1999
DOI: 10.1111/j.1550-7408.1999.tb05141.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Labyrinthulids and Thraustochytrids Based On the Sequencing of 18s Ribosomal Rna Gene

Abstract: Labyrinthulids and thraustochytrids are unicellular heterotrophs, formerly considered as fungi, but presently are recognized as members in the stramenopiles of the kingdom Protista sensu lato. We determined the 18S ribosomal RNA gene sequences of 14 strains from different species of the six genera and analyzed the molecular phylogenetic relationships. The results conflict with the current classification based on morphology, at the genus and species levels. These organisms are separated, based on signature sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 52 publications
6
96
1
Order By: Relevance
“…Because the classifications of thraustochytrids based on morphology and molecular phylogeny do not necessarily agree with each other (21), it is difficult to discuss whether SssRNAV is species specific or strain specific based only on the present results. However, it is notable that the four SssRNAV-sensitive strains (NIBH N1-27, SEK 0209, MBIC 11066, and MBIC 11072) belong to a particular group (Table 1) based on molecular phylogeny (22; R. Yokoyama, personal.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Because the classifications of thraustochytrids based on morphology and molecular phylogeny do not necessarily agree with each other (21), it is difficult to discuss whether SssRNAV is species specific or strain specific based only on the present results. However, it is notable that the four SssRNAV-sensitive strains (NIBH N1-27, SEK 0209, MBIC 11066, and MBIC 11072) belong to a particular group (Table 1) based on molecular phylogeny (22; R. Yokoyama, personal.…”
Section: Resultsmentioning
confidence: 76%
“…They are comprised of six genera (33,47), Althornia (26), Aplanochytrium (2), Japonochytrium (32), Schizochytrium (18), Thraustochytrium (59), and Ulkenia (13). However, it has been shown that the current classification of these genera based on morphology does not agree with the molecular phylogenetic relationships based on the 18S rRNA gene sequences (21). Currently, in order to resolve the confusion regarding the classification and nomenclature of the thraustochytrids, further comparative studies based on morphology, molecular phylogeny, and chemotaxonomy are under way (R. Yokoyama, personal communication).…”
mentioning
confidence: 99%
“…As both approaches also utilize or require ecological (and other) data, combining numerous methods in future efforts should prove beneficial (Carstens et al 2013), and is probably vital to any revision of the group-which has been called for (e.g., Porter 1990;Honda et al 1999). However, as protistan genetic diversity is vastly greater than that within plant, animal or fungal groups, a single genetic marker has not emerged as ideal for approaching species-level investigations, though use of the ITS region has been common (Pawlowski et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thraustochytrids are cosmopolitan apochlorotic stramenopile protists classified in the class Labyrinthulomycetes within the kingdom Chromista (Cavalier-Smith et al 1994, Leipe et al 1994, Honda et al 1999. Based on phylogenetic analysis of 18S ribosomal RNA gene sequences, Honda et al (1999) suggested that thraustochytrid strains belong to either TPG (thraustochytrid phylogenetic group) which is a monophyletic group comprised of only thraustochytrid strains or LPG (labyrinthulid phylogenetic group) which includes all members of the family Labyrinthuraceae and some strains belonging to the family Thraustochytriaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Based on phylogenetic analysis of 18S ribosomal RNA gene sequences, Honda et al (1999) suggested that thraustochytrid strains belong to either TPG (thraustochytrid phylogenetic group) which is a monophyletic group comprised of only thraustochytrid strains or LPG (labyrinthulid phylogenetic group) which includes all members of the family Labyrinthuraceae and some strains belonging to the family Thraustochytriaceae.…”
Section: Introductionmentioning
confidence: 99%